A Clinical Trial of Four Hypnotic Drugs - Riche, W. Harding Le (1966)
A clinical trial of four hypnotic drugs was carried out: Ro 4-5360, 10 mg. (Mogadon), methyprylon, 200 mg. (Noludar), Ro 4-5360, 5 mg. (Mogadon), secobarbital sodium, 100 mg. (Seconal), and a placebo. The study was on the usual double-blind basis, and all observations were made by a full-time nurse. Capsules were given at 10 p.m. for five successive nights, with two nights free from medication or observation. There were five such periods. The nurse carried out her observations right through the night, determining whether the patients were awake or asleep. Each of these drugs was statistically significantly different from the placebo, in terms of length of sleep. Differences between the individual drugs were not significant. The length of action of the various drugs appeared to be similar, with a somewhat longer period of activity for the Mogadon in both dosages. The major side effect was some drowsiness: this was more marked with Mogadon 10 mg. With the hypnotics, the patients had, on the average, about one hour more sleep than on the placebo.